4CPS-108 An investigation into whether an oncology counselling training programme for pharmacists can improve medicines’ optimisation for patients taking first-cycle chemotherapy - Baig, M (Eur J Hosp Pharm, 2018)
BACKGROUND: Adherence to an oncology regime is vital and hence it is important that patients understand how and when to take their medicines before their first cycle of chemotherapy as well as know the signs of toxicity that can be life-threatening. An oncology counselling training programme was developed and an audit was undertaken to assess whether its use by pharmacists in a hospital outpatient pharmacy could improve medicines’ optimisation. PURPOSE: To investigate whether the use of an oncology training programme for pharmacists can improve medicines’ optimisation for patients taking first-cycle chemotherapy. MATERIAL AND METHODS: A counselling tool was developed containing proformas of the most commonly dispensed oral chemotherapy medicines. Pharmacists were trained via a specific programme which taught them how to counsel effectively using the tool. The proformas contained detailed information about how and when to take the drug, what to do if they miss or vomit after taking a dose, what the most common side-effects are and how to manage those side-effects. Fifty-two patients were included in the study. All patients were interviewed to assess how much they knew about their medicines and how confident they were before and after the pharmacists’ counselling. RESULTS: Seventy-five per cent of patients were confident/very confident after counselling by pharmacists compared to 35% prior to it. Patients gained information (despite prior counselling from other health professionals) on: how to take the medicines (31%); what to do if they miss a dose (82%); what to do if they vomit after a dose (86%); how to handle chemotherapy (66%); and what the side-effects are (14%). Interventions, including clarifying the frequency of dosing, alerting doctors about changes in patients’ weight and providing information about drug interactions and how the medicines work were made in 42% of cases. Counselling by the newly trained pharmacists helped 100% of patients. CONCLUSION: Utilisation of an oncology counselling training programme for pharmacists can significantly enhance patients’ knowledge about their first-cycle chemotherapy and boost their confidence about taking their medicines, which can improve medicines’ optimisation and patient safety. No conflict of interest